State audit, budgetary appropriations and their implications to regulatory governance - Muñez, Jephte Olimpo (Philippine Journal of Public Administration, 2013)
With the change of leadership in 2010, a change in regulatory climate has been anticipated. Compliance with statutory requirements and administrative regulations was expected to be further reinforced to strengthen and support regulatory governance reforms through monitoring and control across the main branches of the government, providing symbiotic participation from the private sector and civil society. As defined by law, state audit is "the analytical and systematic examination and verification of financial transactions, operations, and accounts and reports of any government agency for the purpose of determining their accuracy, integrity, and authenticity and satisfying the requirements of law, rules, and regulations." It is a function conducted by the Supreme Audit Institution of the country, grounded on the values of integrity, transparency, and accountability. This article explores the relationship between the extent of budgetary appropriations profile across the national government agencies (NGAs), which includes the executive, legislative, judiciary, and constitutional commission, vis-a-vis the NGAs audit compliance profile.